Study on the Proportion of Conglomerate Similar Materials Based on the Orthogonal Test - Mengze Yang; Yu Yang; Bo Zhao (Shock and Vibration)
Similarity model test is one of the important methods to study the properties of rock engineering. In this paper, quartz sand, 42.5 ordinary Portland cement, and tap water are used as the similar test materials to simulate the properties of conglomerate. The three control factors are cement-to-water ratio, cement-to-sand ratio, and quartz sand particle size, and orthogonal tests are set at four levels. The permeability coefficient, compressive strength, elastic modulus, density, and Poisson’s ratio are tested on specimens of similar materials of conglomerate, and the corresponding physical and mechanical indexes are obtained. The range analysis method is used to analyse the influence of various factors on the mechanical properties. The results show that (1) the physical and mechanical parameters of similar materials have a certain degree of dispersion under different proportions; (2) the proportion of similar conglomerate materials is cement : sand : water : water reducer = 1 : 2 : 0.4 : 0.6%; and (3) multiple linear regression analysis is carried out on the control factors and mechanical parameters to obtain the regression equation of the proportion of similar materials, which proves that the equation could be used to make the study of conglomerate similar materials under the stress coupling of seepage.